ISOLATION AND CHARACTERIZATION OF IAA-PRODUCING RIZOSPHERE BACTERIA FROM RICE PLANTS (ORYZA SATIVA L.) IN KEDUNGPANI URBAN VILLAGE, SEMARANG CITY - Sutrisno Sutrisno (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2021)
Rhizosphere bacteria live in the soil around plant roots. Various rhizosphere bacteria are able to produce the hormone Indole-3-Acetic Acid (IAA) which stimulates plant growth. This study aims to isolate and characterize IAA-producing rhizosphere bacteria in rice plants in the rice fields of Kedungpani urban village, Semarang city. Bacterial enumeration was carried out using the total plate count (TPC) method. The isolates obtained were characterized by observation of colony and cell morphology, gram staining, endospore staining, catalase test, and sugar fermentation test. The ability to produce the IAA hormone was tested using Salkowski's reagent. The enumeration results showed that the total bacteria in the sample was 2.9 x 105 CFU / g. A total of 10 isolates were obtained and were able to produce the IAA hormone with various concentrations. Isolates KP1, KP2, KP3, KP4, KP5, KP6, KP9, KP13, KP14, and KP15 produced IAA with concentrations of 3.389, 5.111, 3.000, 1.667, 1.944, 5.056, 5.444, 4.500, 5.056, and 10.833 ppm, respectively. The results showed that there were 5 isolates with the highest IAA concentrations, namely KP2, KP6, KP9, KP14, and KP15 which had the potential to be used as biostimulant agents for plants.